Humanizing AI-Driven Human Resource Management through Islamic Work Ethics in the E-Commerce Industry - Agus Supriyanto (Lentera Ilmu Nusantara, 2024)
The development of Artificial Intelligence (AI) has driven significant changes in human resource management practices within the e-commerce industry. Through algorithmic management systems, companies utilize AI to monitor, evaluate, and control employee performance in real time to enhance operational efficiency. However, the implementation of such systems has also raised various concerns regarding fairness, employee autonomy, and workplace well-being. This study aims to explore how Islamic Work Ethics (IWE) shape the responses of Muslim employees toward AI-driven management systems in the e-commerce industry in Kudus Regency, Central Java, Indonesia. This research employed a descriptive qualitative approach with a case study design. A total of 15 participants were selected through purposive sampling, consisting of five logistics couriers, five warehouse operational staff members, and five customer service representatives. Data were collected through semi-structured in-depth interviews and document analysis and were subsequently analyzed using thematic analysis. The findings revealed three major themes. First, the value of amanah (trustworthiness) encourages employees to remain honest and responsible despite being subjected to intensive digital surveillance. Second, the principle of ‘adl (justice) serves as the foundation for criticism of automated evaluation systems, which are perceived as not fully reflecting fairness because they overlook the contextual realities of work. Third, the values of ihsan (excellence) and ta’awun (mutual assistance) help employees cope with algorithm-based performance pressures by maintaining work quality and strengthening solidarity among workers. This study concludes that Islamic Work Ethics function as a moral foundation capable of humanizing the implementation of AI in the workplace. The integration of AI technologies with ethical values is essential for creating human resource management systems that are not only efficient but also fair, inclusive, and sustainable.